"Ghost peaks" of olmesartan medoxomil: Two solution degradation products of olmesartan medoxomil via oxidation mediated by metal ions. (28th March 2022) - Huang, Minxia; Yao, Beiyang; Jiang, Manhua; Sun, Fuzhou; You, Jinsong; Huang, Fangfang; Zhao, Yanping; Wu, Shuming; He, Xinqian; Song, Xuezhi
Abstract: Two unknown solution degradants were found during the dissolution testing in 0.1‐M HCl for olmesartan medoxomil (OLM) tablets. The structure of the degradants was identified and characterized by liquid chromatography–ultraviolet (LC–UV), liquid chromatography with tandem mass spectrometry (LC–MS/MS), and nuclear magnetic resonance (NMR) and demonstrated to be cyclization of tetrazole and benzene in the olmesartan (OL) and OLM structures. A series of studies including stress studies, simulation studies, and mechanism‐based studies were performed to reveal the potential mechanisms that lead to the formation of the unknown degradants. The study results demonstrated that the degradation was catalyzed with radicals that originated from the metal ions leached from the inner surface of high‐performance liquid chromatography (HPLC) glass vials with dissolved oxygen under acidic condition. Prerinsing the glass vials with acidic solution dissolved with EDTA can effectively avoid the generation of such oxidative impurities. The present work provides new insights into the understanding of degradation pathways of OLM, which might support the development of OLM tablets.